2009
DOI: 10.1139/f09-077
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective growth analysis of Atlantic salmon (Salmo salar) from the Miramichi River, Canada

Abstract: We have developed a multidecadal retrospective growth history for the principal sea-age groups of the Miramichi River population of Atlantic salmon ( Salmo salar ) that characterizes freshwater growth and marine growth partitioned on a number of different time scales. Based on precedent with European salmon, we tested whether postsmolt growth was positively correlated with recruitment, assuming that growth during the postsmolt year mediates predation mortality. We found no such correlation in the Miramichi pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 52 publications
6
33
0
Order By: Relevance
“…The proposed recruitment mechanism draws on a phenological mismatch between thermal conditions in fresh water and the ocean that delivers post‐smolts into warmer ocean conditions with a more aggressive predator field. This mechanism has been proposed for stocks in the Gulf of St Lawrence, which represent trends in the stock complex (Friedland et al. 2003b, 2009b), and specifically for stocks in the GOM (Friedland et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed recruitment mechanism draws on a phenological mismatch between thermal conditions in fresh water and the ocean that delivers post‐smolts into warmer ocean conditions with a more aggressive predator field. This mechanism has been proposed for stocks in the Gulf of St Lawrence, which represent trends in the stock complex (Friedland et al. 2003b, 2009b), and specifically for stocks in the GOM (Friedland et al.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from wild populations comes from river systems in both Canada and the United States including: the Margaree stock from Nova Scotia (Friedland et al. 2005); the Machias and the Narraguagus rivers of coastal Maine (Hogan & Friedland 2010); and the Miramichi River, the largest salmon‐producing river in North America (Friedland et al. 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative data from modern Atlantic Salmon scales2930 as well as European505152 and North American53 archaeological bones were sourced from previously published studies and are supplemented by new analyses of a single European Atlantic Salmon individual from an Early Christian context from the site of Knowth in Ireland. Morphological analyses of scales from 5 of the 7 nineteenth-century Atlantic Salmon skin mounts were used to provide a second line of evidence for salmon origin and were conducted at the National Marine Fisheries Service (Narragansett, RI, USA) using established methods5455 (Supplementary Information). …”
Section: Methodsmentioning
confidence: 99%
“…The reasons for this difference in growth rate are not clear, and exceptions exist (Friedland et al 2009a). In the west Atlantic, Saunders (1969) and Anderson (1985) suggested that grilse and MSW salmon have different migration routes at sea.…”
Section: Discussionmentioning
confidence: 99%